Adult neurogenesis in neurodegenerative diseases - Winner, Beate; Winkler, Jürgen (Cold Spring Harbor Perspectives in Biology, 2015)
Adult neurogenesis is limited to specific brain regions in the mammalian brain, such as the hippocampal dentate gyrus and the subventricular zone/olfactory bulb system. Alterations in adult neurogenesis appear to be a common hallmark in different neurodegenerative diseases including Parkinson's disease (PD), Alzheimer's disease (AD), and Huntington's disease (HD). This is remarkable, because the distinct pathological proteins responsible for the different diseases induce the loss of different neural populations. Impaired adult neurogenesis was shown in numerous animal models of neurodegenerative diseases; however, only few postmortem studies have been performed. We will review concepts related to the interplay between cellular plasticity in regions of adult neurogenesis with a specific focus on cell-autonomous and non-cell-autonomous factors. Furthermore, various strategies aimed to stimulate neuronal plasticity will be discussed within the context of a potential translation into therapeutic approaches for neuropsychiatric symptoms associated with PD, HD, and AD.
EVALuna2:25348